Psychotic and Substance Use Disorders Among Relatives of Patients with Bipolar Disorder at a Hospital in Kenya - Kimutai Katwa; Benson Gakinya; Irene Chesire; Maloosoy Katwa; Nicodemus Kuboi (Pan-African Journal of Health and Environmental Science)
Background: Bipolar disorder is one of the most prevalent psychiatric conditions in Kenya. Studies conducted outside Kenya show that bipolar disorders and psychotic disorders are interlinked by family relations, while alcohol and substance use disorders are their important comorbidities. This study investigated the prevalence and associated factors of psychotic, alcohol and substance use disorders among first-degree relatives (FDR) of patients with bipolar disorders at a referral hospital in Western Kenya.